The developmental history of athletes questionnaire : towards a comprehensive understanding of the development of sport expertise. - Hopwood, M. (2013)
Knowledge of the training requirements and environmental factors associated with expert sports performance is essential for the design of effective sport programs and the creation of nurturing practice environments. However, several limitations in the sport expertise development literature restrict the application of current knowledge to practical settings. Results and recommendations from existing studies are inconsistent, with discrepancies likely related to a combination of small, homogenous sample sizes and differences in measurement tools. Furthermore, the questionnaires and interview guides utilized are generally poorly validated. To begin to address these limitations, the Developmental History of Athletes Questionnaire (DHAQ) was constructed and rigorously validated. Results highlighted a number of issues related to reliability of retrospective recall and sub-optimal questionnaire design. In an attempt to resolve these issues, modifications were made to the DHAQ, and it was converted to an online format to allow large scale distribution. Following modification and conversion, the DHAQ was subjected to further reliability analyses. While several reliability issues were still apparent and several further revisions were required, the amendments markedly strengthened the measurement tool and the DHAQ can now start to be utilised in investigations of sport expertise development. Continued assessments of validity of the updated, online DHAQ are recommended; however, it is proposed that the DHAQ be considered the emergent standard tool for the collection of athlete developmental history information, providing a major contribution towards a comprehensive understanding of the development of sport expertise.